USING PREZI PRESENTATION AS INSTRUCTIONAL MATERIAL IN ENGLISH GRAMMAR CLASSROOM - Rahmat Yusny; Desi Nanda Kumita (Englisia: Journal of Language, Education, and Humanities, 2016)
Utilizing digital technology as a medium for educational instruction has now become one of the 21 century pedagogy trends. Numerous researches suggested that using digital technology provides positive impacts as it gives more access to resources for the learning. In Foreign language pedagogy, using digital technology fosters learnersâ€™ autonomy by self-managing the amount of learning inputs outside the classroom. However, many studies emphasize more on the communicative and the vast resources accessible for the learners. Very limited attention given to the impact of the visual aid that focuses on aesthetic values of instructional design. English Grammar is one of many subjects that often received complaints by learners and claimed as a â€œboringâ€ subject. Many English teachers especially in developing countries still utilize traditional method in teaching grammar. They introduce sentence structure using grammar formulas. Although, this method is still very popular, it often considered monotonous by many learners. This paper discusses about the study of using Prezi.com presentation to deliver grammar instruction materials in an English language classroom. From the study, it was found that the majority of the students involved in the study are fond of the materials and the post-test results showed grammar mastery improvement after receiving a grammar lesson that shows instructional materials using prezi. On the other hand, the control class that uses only writing boards and worksheets showed less improvement. This research provides new technique in developing grammar instruction design using a web tool called Prezi in enhancing the display of the instruction material. The experiment was given to students of English Language Education. The result of the study shows studentsâ€™ positive perception toward the use of Prezi in English grammar instructional material.